Development of an Evaluation Checklist for Localized Chinese Language Textbooks in Sri Lanka - Dassanayake, Noel (Bina Nusantara University, 2022)
The research analyzed the limitations of existing Chinese language textbooks in Sri Lanka and proposed a tentative checklist for evaluating localized Chinese language textbooks. The discourse on the effectiveness of global textbooks in local contexts and the need for evaluating such textbooks had seen new paradigm shifts in parallel to the transformations in new language environments. A majority of the institutes and programs teaching Chinese as a Foreign Language in Sri Lanka were using global CFL textbooks as their main study material, and their effectiveness had not yet been evaluated by researchers. The research conducted a quadruple perspective analysis, including an online survey with learners and teachers to examine the issues in existing CFL textbooks, a review of existing literature on textbook evaluation, an analysis of existing CFL textbooks in Sri Lanka, and an examination of existing language textbook evaluation criteria. The findings of the survey indicate that global textbooks have not catered to the specific language requirements of the informants. Insensitivity to the local and regional cultural content, minimal utilization of learners’ L1 repertoire, ambiguous inapt translation of vocabulary, and market-oriented presentation of teaching-learning content is found to be core issues, and high pricing and inaccessibility also are influential issues. Based on the quadruple perspective analysis, the research has developed a tentative evaluation checklist of 37 items with a specific emphasis on localization and culture sensitivity.